(untitled) (Research, Society and Development, 2022)
Introduction: Hospitalized children are more susceptible to the worsening of a disease, due to the fragility of their own age. As a large part of pediatric diseases requires physical therapy, physical therapy can contribute to reducing hospital stay, as well as the morbidity of this age group. Objective: To carry out a survey using the electronic medical record, the most prevalent diseases and the physiotherapeutic approaches used with children in a public hospital in the countryside of Bahia. Methodology: This is a cross-sectional, descriptive, quantitative study carried out based on documentary analysis of 20 medical records of children who underwent physical therapy between the months of December 2018 and March 2019. Results: Most children were male (55%), and the number of hospitalizations for children under 2 years was considerably higher (55%) in relation to other ages. Regarding the length of stay (55%), they spent 4 to 7 days in the pediatric sector and the average hospital stay was 5.6 days ± 1.4. With regard to the number of physical therapy procedures performed, the predominance was 6 to 9 sessions (45%) and most of the causes of hospitalizations were related to diseases of the respiratory system (55%). As for the conducts performed, it was found that the majority corresponded to respiratory physiotherapy, followed by motor kinesiotherapy. Final considerations: The results showed that both the most prevalent diseases, as well as the physiotherapeutic conduct performed with children in this hospital, were the vast majority of respiratory order.